El trabajo infantil y su influencia en el desarrollo social de los niños del barrio Isidro Ayora del cantón Catamayo, en el año 2024. - Paredes Agreda, Yaleny Monserrate (2024)
Child labor is a reality that affects a large number of children around the world. To address this problem, this research was developed to find out the influence of child labor on the development of children in the Isidro Ayora neighborhood. This study is a descriptive research, with a mixed methodology that combines quantitative and qualitative approaches and an analytical method. The quantitative methodology is applied to the collection of information with the use of qualitative techniques such as semi-structured interviews, surveys and direct observation which were applied to child who lived in "Isidro Ayora neighborhood of Catamayo Canton" and the qualitative methodology in the explanation of its characteristics. The results highlight that the causes of Child Labor are the lack of economic resources and the limited availability of basic needs. In addition, the consequences of Child Labor, it is noteworthy that these affect their physical, emotional and social well-being. Among the characteristics of child labor, the most common is the age of 7 years, who work at least 6 hours a day, either in evening shifts during the week or all day on weekends. Income varies between 5 and 20 dollars, depending on the activity, which includes street vending, agricultural work and domestic work. Children, assuming adult labor responsibilities at an early age, require urgent interventions to ensure their well-being and proper development.